An Aptamer Sensor Based on Alendronic Acid-Modified Upconversion Nanoparticles Combined with Magnetic Separation for Rapid and Sensitive Detection of Thiamethoxam - Qian Huang; Lu Han; Hui Ma; Weijie Lan; Kang Tu; Jing Peng; Jing Su; Leiqing Pan (Foods)
The widespread use of thiamethoxam has led to pesticide residues that have sparked global concerns regarding ecological and human health risks. A pressing requirement exists for a detection method that is both swift and sensitive. Herein, we introduced an innovative fluorescence biosensor constructed from alendronic acid (ADA)-modified upconversion nanoparticles (UCNPs) linked with magnetic nanoparticles (MNPs) via aptamer recognition for the detection of thiamethoxam. Through base pairing, thiamethoxam-specific aptamer-functionalized MNPs (apt-MNPs) were integrated with complementary DNA-functionalized UCNPs (cDNA-UCNPs) to create the MNPs@UCNPs fluorescence biosensor. Thiamethoxam specifically attached to apt-MNPs, leading to their separation from cDNA-UCNPs, which in turn led to a reduction in fluorescence intensity at 544 nm following separation by an external magnetic field. The change in fluorescence intensity (ΔI) was directly correlated with the concentration of thiamethoxam, enabling the quantitative analysis of the pesticide. With optimized detection parameters, the biosensor was capable of quantifying thiamethoxam within a concentration span of 0.4–102.4 ng·mL−1, and it achieved a detection limit as minute as 0.08 ng·mL−1. Moreover, leveraging the swift magnetic concentration properties of MNPs, the assay duration could be abbreviated to 25 min. The research exhibited a swift and precise sensing platform that yielded promising results in samples of cucumber, cabbage, and apple.